(3GdfaMGJ GdbOhSjI Ydi GdCSeGA GdEOQjSjIs - (3GdfMQjQj, GdMfaj, GdTfGhj, YKeGf GdfMQjQjs
(3ChdgG (B:s
(3GdMeO ddg GdPj dG jUOQ aj GdhLhO ehLhO EdG hdg ajg MceIhHYO ajbhdYKeGf GdfMQjQj GdMfaj GdTfGhjJJYdb HGdcdGe Ydi GdCSeGA hSejJgG GdfaMGJ GdbOhSjIs
(3BNQgG (B:s
(3fGbU GdBNQ, hBNQgGSQGajd aef CQGO Cf jbQC OYhI HTeN fXQ ChdG GdTeS aj Cj HQL gj hCj GSe jJYdb HPdc GdHQO jHOC ajHOCs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf(B: 2 / 666s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdJUha hGdBOGH GdTQYjIs